2016
DOI: 10.1039/c5ay02086g
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of photo-oxidative alterations to natural organic matter in water using fluorescence excitation emission matrices and liquid chromatography-organic carbon detection techniques

Abstract: Fluorescence excitation emission matrices (FEEMs) and liquid chromatography-organic carbon detection (LC-OCD) are relatively novel techniques currently used for analysing natural organic matter (NOM) in water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 26 publications
1
4
0
Order By: Relevance
“…In fact, this observation is supported by the other five LC‐OCD analyses for the centre point condition and the four axial point conditions in the DOE method; refer to Figure S‐2 in the Supplementary Material. A previous study reported a similar observation related to the treatment of surface water containing NOM and attributed it to the decomposition of particulate matter . For those conditions that achieved COD removals greater than 70 % (i.e.…”
Section: Resultssupporting
confidence: 63%
See 4 more Smart Citations
“…In fact, this observation is supported by the other five LC‐OCD analyses for the centre point condition and the four axial point conditions in the DOE method; refer to Figure S‐2 in the Supplementary Material. A previous study reported a similar observation related to the treatment of surface water containing NOM and attributed it to the decomposition of particulate matter . For those conditions that achieved COD removals greater than 70 % (i.e.…”
Section: Resultssupporting
confidence: 63%
“…For the wastewater 1 sample (shown in Figure a), the positions of the peaks were the same but the sizes of the peaks increased. Specifically, the size of peak 1 increased by approximately 40 %; it is hypothesized that this result is due to the transformation of particulate matter into dissolved DOC . For the wastewater 2 sample (shown in Figure b), the change in the chromatogram was much more drastic.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations